Management Teachers in the Implementation of Learning Process In The Industrial Revolution 4.0 - Mulyani, Tati; Harapan, Edi; Kesumawati, Nila (Journal of Social Work and Science Education, 2022)
This study attempts to teacher management class in the implementation of learning process of SD Negeri 10 Banyuasin III in the industrial revolution 4.0. Qualitative was used of this research. Informants were the principals and 10 teachers of SD Negeri 10 Banyuasin III. Data collection technique using a questionnaire. The results suggest that teacher management class in the implementation of the learning process had been considered good and capable on management implementation of the learning process. The obstacles were lack of skill in new technologies.